Genetic analysis of the recG locus of Escherichia coli K-12 and of its role in recombination and DNA repair. - Lloyd, R G (1991)
We describe a transposon insertion that reduces the efficiency of homologous recombination and DNA repair in Escherichia coli. The insertion, rec-258, was located between pyrE and dgo at min 82.1 on the current linkage map. On the basis of linkage to pyrE and complementation studies with the cloned rec+ gene, rec-258 was identified as an allele of the recG locus first reported by Storm et al. (P. K. Storm, W. P. M. Hoekstra, P. G. De Haan, and C. Verhoef, Mutat. Res. 13:9-17, 1971). The recG258 mutation confers sensitivity to mitomycin C and UV light and a 3- to 10-fold deficiency in conjugational recombination in wild-type, recB recC sbcA, and recB recC sbcB sbcC genetic backgrounds. It does not appear to affect plasmid recombination in the wild-type. A recG258 single mutant is also sensitive to ionizing radiation. The SOS response is induced normally, although the basal level of expression is elevated two- to threefold. Further genetic studies revealed that recB recG and recG recJ double mutants are much more sensitive to UV light than the respective single mutants in each case. However, no synergistic interactions were discovered between recG258 and mutations in recF, recN, or recQ. It is concluded that recG does not fall within any of the accepted groups of genes that affect recombination and DNA repair.